Assessment and evaluation of narratives in guided imagery and music (GIM) - Perilli, Gabriella Giordanella (Barcelona Publishers, 2017)
The author presents a new paradigm for GIM theory, research, and practice-one that adds new dimensions yet retains the integrity of the method. The main focus is on how both client and therapist can derive meaning out of the narratives that emerge in the GIM session. The paradigm consists of a new procedural component to the session, the use of cognitive concepts to analyze the narratives created by the client, and a method of assessment and evaluation. The new procedure is the "re-descriptive technique," wherein the client writes a description of the GIM experience at home, after having time